1996
DOI: 10.1111/j.1600-0897.1996.tb00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines of the Human Reproductive Tract

Abstract: HOF contains a high level of IL-10 (588 +/- 304 pg/mL), a powerful immune suppressor which probably plays a role in regulating immune responses in the fallopian tube and possibly in the endometrial cavity. Our observations suggest that seminal plasma with its huge content of TGF beta provides immune protection for sperm. Unfortunately, such high concentrations of TGF beta may also inhibit an immune defense in any organ in which semen is deposited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(82 citation statements)
references
References 23 publications
3
78
1
Order By: Relevance
“…Hanna et al [22] also indicate that tissues from normal pregnancies expressed predominantly IL-10. Similarly, Srivastava et al, [23] explain that the high IL-10 levels in human oviductal fluid plays a powerful role in regulating immune responses in the fallopian tube and endometrial cavity. IL-10 is a potent TH2 type cytokine and its deficiency in patients with eclampsia in this study in relation to increased TNF-α levels in same individuals may explain the adverse clinical outcome of eclampsia (50%) child and 22% maternal mortality) compared to normal pregnant women with equally high levels of TNF-α but adequately compensating levels of IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Hanna et al [22] also indicate that tissues from normal pregnancies expressed predominantly IL-10. Similarly, Srivastava et al, [23] explain that the high IL-10 levels in human oviductal fluid plays a powerful role in regulating immune responses in the fallopian tube and endometrial cavity. IL-10 is a potent TH2 type cytokine and its deficiency in patients with eclampsia in this study in relation to increased TNF-α levels in same individuals may explain the adverse clinical outcome of eclampsia (50%) child and 22% maternal mortality) compared to normal pregnant women with equally high levels of TNF-α but adequately compensating levels of IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Human milk, especially colostrum, contains many materials such as cytokines (TGF␤, EGF, etc) and sIgA. 1 The present trial is still preliminary and the efficacy of colostrum therapy for gut GVHD should be confirmed in more cases. In the same setting oral immunoglobulin may be an alternative choice.…”
Section: Colostrum and Severe Gut Gvhdmentioning
confidence: 99%
“…This result agrees with Blakewood et al [2,3] who found a high percentage of morula and blastocyst after culture of preimplantation mammalian embryos in the amniotic cavity of chick embryos. This development-promoting ability of CEAF is possibly due to the presence of several growth factors that have previously been found in the amniotic fluid of other species such as, TGF, IGF, stem cell factor (SCF) in human amniotic fluid [3,7,19], IGF in turkey amniotic fluid [15], vascular endothelial growth factor (VEGF) in ovine amniotic fluid [4], and hematopoietic growth factors in human amniotic fluid [6]. However a careful biochemical study is needed to find the precise concentrations of growth factors in CEAF.…”
Section: -4644mentioning
confidence: 99%